Effects of EPO combined with mild hypothermia on oxidative stress and neuroprotection in neonates with hypoxic-ischemic encephalopathy: Oxidative stress and neuroprotection in neonates - Xu, Ying; Huang, Li; Han, Jinan; Zhou, Yan (Cellular and Molecular Biology, 2022)
After perinatal asphyxia, hypoxic-ischemic encephalopathy (HIE) in term infants produces long-term neurologic sequelae or death. Obtaining a reliable, evidence-based prognosis is critical. Therapeutic hypothermia is a suggested treatment for newborn babies with moderate-to-severe HIE at or near term. However, this treatment is unsuccessful in a significant proportion of newborns. This sparked a worldwide hunt for neuroprotectants that may enhance the effects of mild hypothermia. We look at erythropoietin (EPO) as a possible possibility. This research aimed to see how EPO paired with moderate hypothermia affects oxidative stress and neuroprotection in newborns with HIE. Children with HIE diagnosed and treated at the hospital were first recruited as research participants and split into two groups using a random number system. The control group got mild hypothermia therapy as part of their standard treatment, whereas the EPO group received EPO therapy in addition to mild hypothermia therapy. Statistical analysis techniques such as the Mann-Whitney U test, Chi-squared test, and t-test were used to examine the effects. The data show that the efficacies of combination therapy of mild hypothermia and EPO for infant HIE seem to be promising right now.